Biomaterials Act as Enhancers of Growth Factors in Bone Regeneration. (28th October 2016) - Chen, Rui; Wang, Jing; Liu, Changsheng
Abstract : Inspired by the physiological events of the "wound healing cascade", the integration of biomaterials and growth factors is generally accepted as an emerging and powerful strategy for bone regenerative therapy. As a type of biological mediator, growth factors play a key role in functional bone regeneration. In this review, recent progress in the enhancement of bone‐related growth factors via a biomaterial strategy will be discussed. Two main reinforcing mechanisms, temporal regulation and efficacy manipulation, are described in detail, highlighting the potential capability of biomaterials to harness the interactions between growth factors and specific cells. The effects of biomaterials for promoting bone formation via growth factor‐mediated osteogenesis are further elucidated. Finally, an outlook of the prospects in terms of superior communication among growth factors, cells, and biomaterials in the microenvironment is presented, which might provide new directions for the design of medical devices for bone regeneration. Abstract : Biomaterials act as enhancers of growth factors in bone regeneration via two mechanisms: temporal regulation and efficacy manipulation. This results in extended growth factor half‐lives due to effective loading and sustained release, as well as enhanced bioactivity mediated by growth factor‐receptor recognition driven by the optimal orientation of growth factors and receptor localization.